184k views
0 votes
If g(x) = x-3/x+6, find: a. g(0) =b. g(3) =c. g(4) =d. g(6) =e. g(- 6) =

If g(x) = x-3/x+6, find: a. g(0) =b. g(3) =c. g(4) =d. g(6) =e. g(- 6) =-example-1
User Joselyn
by
4.5k points

1 Answer

4 votes

The Solution:

Given:

Required:

Find:


(a)\text{ }g(0)=(0-3)/(0+6)=(-3)/(6)=-(1)/(2)
(b)\text{ }g(3)=(3-3)/(3+6)=(0)/(9)=0
(c)\text{ }g(4)=(4-3)/(4+6)=(1)/(10)
(d)\text{ }g(6)=(6-3)/(6+6)=(3)/(12)=(1)/(4)
g(-6)=(-6-3)/(-6+6)=(-9)/(0)\text{ = undefined}
g(-6)=(-6-3)/(-6+6)=(-9)/(0)\text{ = undefined}

If g(x) = x-3/x+6, find: a. g(0) =b. g(3) =c. g(4) =d. g(6) =e. g(- 6) =-example-1
User Headwinds
by
5.2k points